Clinical epidemiology of hand eczema in patients accessing dermatological reference centres: results from Italy. (1st January 2015) - Scalone, L.; Cortesi, P.A.; Mantovani, L.G.; Belisari, A.; Ayala, F.; Fortina, A.B.; Bonamonte, D.; Borroni, G.; Cannavò, S.P.; Guarneri, F.; Cristaudo, A.; De Pità, O.; et al.
Summary: Background: Data on the epidemiological impact and clinical characteristics of chronic hand eczema in Southern Europe are lacking. Objectives: To estimate the prevalence of chronic hand eczema in its different stages of severity and refractoriness to standard therapy in patients accessing Italian dermatological reference centres, and to evaluate sociodemographic and clinical factors associated with each stage. Methods: A cross‐sectional multicentre study was conducted. Adult patients with hand eczema, consecutively accessing 14 centres over a 6‐month period, were enrolled. Patients were classified according to disease duration, severity and response to standard therapy with potent topical corticosteroids. Logistical regression was performed to investigate the relationship between sociodemographic and clinical data with different stages of eczema. Results: The total number of participants was 981. Hand eczema was chronic in 83·5% of patients; 21·3% had severe eczema, with 62·0% of these patients refractory to standard therapy. Food processing and related work, the health professions, craft and related trade works (building, plumbing, electrical), hairdressing/beauty and handicraft work were most frequently associated with chronic hand eczema. Severe chronic hand eczema was more likely to be seen in men, older patients and those with less education. Severe and refractory hand eczema was also more likely among the unemployed and patients with allergic rhinitis and/or atopic dermatitis. Conclusions: Chronic hand eczema is frequent among patients with hand eczema accessing dermatology centres. Many patients were severe and refractory to standard therapy. The appropriate identification of hand eczema is the first step in implementing effective and efficient treatments.